Ankle Motion Is Associated With Soft Tissue Displacement in the Dorsal Thigh: An in vivo Investigation Suggesting Myofascial Force Transmission Across the Knee Joint - Wilke, Jan; Debelle, Heloise; Tenberg, Sarah; Dilley, Andrew; Maganaris, Constantinos (Frontiers in Physiology, 2020)
Experiments in cadavers have demonstrated significant mechanical interactions between constituents of myofascial chains. However, evidence for such force transmission effects is scarce under in-vivo conditions. The purpose of this trial was to examine the impact of ankle motion on soft tissue displacement of the dorsal thigh. Eleven healthy active individuals (26.8±4.3 yrs., six males), in prone position and with the knee extended, underwent passive calf stretches (ankle dorsal extension) imposed by an isokinetic dynamometer. High-resolution ultrasound was used to simultaneously capture the displacement of the semimembranosus muscle, which was quantified by means of cross-correlation analysis. Inactivity of the leg muscles was controlled using surface electromyography (EMG). One participant had to be excluded due to major EMG activity during the experiment. According to a one-sample t test testing the difference to the neutral zero position, ankle dorsal extension induced substantial caudal muscle displacements (5.76±2.67 mm, p<.0001). Correlation analysis (Spearman), furthermore, revealed a strong association between maximal dorsal extension and semimembranosus motion (rho=0.76, p=.02). In conclusion, the present trial provides initial in-vivo evidence for a mechanical force transmission between serially-connected skeletal muscles. This means that local alterations of the mechanical tissue properties may modify flexibility in neighboring (superior or inferior) joints.